Gender and management. Stereotypes and attributions for a successful career - Conceição, N. (2017)
The experiment reported here belongs to a larger research project, which aims at analyzing the effects of gender representation and expectations on the perception of managerial power and success. In this experiment 240 high school students of both sexes received a short description of a successful manager.